Maternal Mortality : Report June, 1932 (London : The Maternal Mortality Committee)
1932-06 1932 1930s 20 pages (8) Convalescent Home Treatment for mothers after confinement. This is stated to be used in eleven Boroughs. (9) District Nursing Associations. Payments can be made for midwifery and maternity nursing, or for the nursing of puerperal fever. Assistance can be given towards the establishment of new Nursing Associations in areas where a midwife is required. It is stated that this is made use of in nineteen Boroughs. (10) Provision can also be made for assisting unmarried mothers and their children. This provision appears to be used by five Boroughs. We have not included Public Assistance accommodation except when special facilities are attached, nor diocesan and voluntary homes unless a grant is made by the Local Authorities. Roughly speaking, it appears that about seventeen Metropolitan Boroughs are aiding the Maternity Service of the district by putting into force half or more of the services they have power to provide. A number of Authorities have made extensions or improvements in their Maternity Services during the past year or so, and these have not yet had time to mature or exercise any definite effect. It would appear from our investigations that while some Authorities are using a large percentage of their powers, none are using them entirely. We must continue our efforts unrestingly until this slur on our citizenship is removed. Sir George Newman divided the recommendations of the Interim Report of the Departmental Committee on Maternal Mortality and Morbidity into three headings :— (1) The necessity of effective ante-natal supervision; (2) Better education of the medical student in the practice of obstetrics; and (3) The institution of an improved and comprehensive national maternity service. As all recommendations on the subject of Maternal Mortality and Morbidity, including our own, come under this grouping, we make our comments on the Reports in this order. Ante-natal Supervision. It will be remembered that the Interim Report of the Maternal Mortality Committee traced 17 per cent. of the 2,000 deaths investigated by them to the lack of ante-natal supervision. (12) 292/824/1/58